KECEPATAN PEMAHAMAN MAKNA DALAM PEMETAAN SASTRA KONTEMPORER MAHASISWA PRODI BAHASA DAN SASTRA INDONESIA - Ikawati, Any; Umamy, Etty (Jurnal Likhitaprajna, 2018)
An understanding of the competencies of each individual varies, especially if correlated with improving the quality of human resources in developing education that has high quality. Therefore, researchers want to carry out research related to how the speed of students of language study programs and Indonesian literature can understand meaning by mapping contemporary literature.Â This research is a qualitative descriptive research that is to describe the ability of students to understand meaning in using contemporary literary mapping. Data collection methods used are observation, interviews and documentation. The subjects of this study were students. Analysis of the data will be conducted qualitatively to determine the ability of students to understand meaning in using contemporary literary mapping.Keywords: speed, understanding, meaning, mapping, contemporary